The Greek public debt problem - Nikiforos, Michalis; Papadimitriou, Dimitri B.; Zezza, Gennaro (Nova Economia, 2016)
The present paper examines the issue of the Greek public debt. After providing a historical discussion, we show that the austerity of the last six years has been unsuccessful in stabilizing the debt while, at the same time, it has taken a heavy toll on the economy and society. The recent experience shows that the public debt is unsustainable and therefore a restructuring is needed. An insistence on the current policies is not justifiable either on pragmatic or on moral or any other grounds. The experience of Germany in the early post-WWII period provides some useful hints for the way forward. A solution to the public debt problem is a necessary but not sufficient condition for the solution of the Greek and European crisis. A wider agenda that deals with the malaises of the Greek economy and the structural imbalances of the Eurozone is of vital importance.